ANALYSIS AND INTERPRETATION THE SYMBOLS USED IN WALL-E MOVIE - IKA TRISNANTASARI (Fakultas Sastra Universitas Gresik, 2018)
WALL-E movie is one of a science fiction animated tells us the audience about global warming issues. Symbols are such as objects, signals, gestures, signs, and words that help people to understand the world. Related to this research, the aim is for interpreting and analyzing the symbols used in the WALL-E movie. This is qualitative research. This research material derived from several sources and transcripts related to WALL-E movie are classified are used as a staple whereas the research used an interpretation theory related to the symbols used in this movie then analyzing it all. Throughout the movie, there are symbols with deeper meanings. These results indicate that there are six symbols in this movie. WALL-E movie spotlight the broken environmental management which is done by human beings themselves. In order to clean the earth, the human was replaced by robots. The moral issue in WALL-E movie can be reflected in real life, relation to the structuring and environmental management with the interests of the environment in any action relating to all elements of the environment.